Biblioteki naukowe i instytucje kultury jako miejsca kwerend genealogicznych. Poradnik w świadczeniu usług informacyjnych na temat materiałów do badań nad genealogią - Naplocha, Anna (In Gremium. Studies in History, Culture and Politics, 2022)
Genealogy research is becoming an increasingly popular hobby and a way to answer the question "where do we come from". In times of increased availability of digital sources, an increasing number of amateur family genealogists have the opportunity to search for their ancestors. Due to the fact that people doing genealogical searches are also becoming more and more frequent guests of scientific libraries, this article is a response to this phenomenon in terms of providing information services by librarians. The article deals with the history of genealogical research in Poland, the threefold division of motivating genealogical queries by enthusiasts of family history, as well as a guide for librarians with a list of sources important for readers looking for information on the genealogy of their family, divided into traditional and electronic databases.